Accounting Standards and Reporting Efficiency in Tabaco City’s Local Government Unit - Camu, Charls Nixon; Brizuela, Sharmaine; Felix, Francine D.; Magbanua, Zsara Byanca B.; Marcelo, Mikyla Jane B.; Lanwang, Azalea Mae B.; Engay, Federico B.; Martirez, Katherine C. (International Journal of Research in Interdisciplinary Studies, 2025)
Accounting systems play an important role in economic and socially developed municipalities and cities, serving to improve the accountability of politicians and the improvement of public service management, and leading in turn to efficient and effective governance. Findings of the study shows that the level of accounting standards and reporting practices in the Local Government Unit of Tabaco City rated the five indicators along preparation with very highly practiced adjectival description with the following numerical ratings: financial reports on time with the highest weighted mean of 4.61 followed by provides documents on financial transactions whenever needed with 4.58; organizes financial documents orderly and chronologically has 4.55 these three indicators have an adjectival description of very highly practiced while the indicator facilitates the easy flow of financial transactions got a weighted mean of 4.48 and communicates the transaction data and information whenever necessary with 4.36, both the same adjectival description of highly practiced. Based from the, the following conclusions are drawn; the results show that the respondents perceived that the level of practice of accounting standards and reporting in the Local Government Unit of Tabaco City along preparation, disbursement and reporting is highly practiced, among the factors that affect the implementation of accounting standards and procedure along the three (3) identified components, the top three factors are: stakeholder requirements, policies and procedure for disbursement and ethical considerations. A recommendations were offered to enhance compliance, transparency, and efficiency in the implementation of accounting standards and the reporting system in an LGU, the following recommendations should be considered.